Parents' need for advice : cooperation between preschool teachers and parents - Jónína Sæmundsdóttir; Sólveig Karvelsdóttir (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 Parents of young children in Iceland hav expressed their need for advice in their parental role, especially regarding discipline. Their opininon is that preschool teachers are the ones who should give advice while children attend preschool. The purpose of this study was to examine if advice to parents is a part of the job of preschool teachers in Iceland and if so to what extent and what kind of advice is given.